Investigating the immersion of inquiry in lecture in improving students’ understanding about scientific inquiry - Muntholib Muntholib; Sri Rahayu; Naif Alsulami; Mohd Shafie Rosli (LPMPP Universitas Negeri Yogyakarta, 2022)
This study aimed to examine the extent to which scientific inquiry procedures during a lecture improvelead to an improvement in students’ understanding of scientific inquiry. The study implemented a one-group pretest-posttest design. Participants were 53 first-year students from the Chemistry Department atin a public university in Malang Ccity. Students’ understandings of scientific inquiry were assessed before and after the instruction using the Views About Scientific Inquiry (VASI) questionnaire. TThe participants’ responses were analysed descriptively and classified into three categories: informed, partially informed, and naïve, with Cohen’s inter-rater reliability value of 0.81.he participants’ responses were analysed descriptively and classified into three categories, namely informed, partially informed, and naïve views with Cohen’s inter-rater reliability value of 0.81. The results showed that (1) before treatment, students' understanding of scientific inquiry was at the level of partially informed and naïve, and (2) the immersion of scientific inquiry procedures in lectures improved students' understanding of scientific inquiry with the improved strength of Cohen's d-effect size was 1.10 (much larger than the typical category) or average normalized gain was 0.3 (medium category).